Negosiasi dan Teknik Lobi sebagai Strategi Komunikasi dalam Meningkatkan Efektivitas Kolaborasi Antarpihak - Henry Arya Ardiansyah; Bagus Maulana Ramadhan; Ivan Aditia Putra; Muhamad Nazril Hidayat; Imam Budiansyah (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
This article discusses the implementation of negotiation strategies and lobbying techniques as participatory communication approaches in the context of community service in Parigi Village, Cikande Sub-district, Serang City. Through intensive community organizing, this activity aims to strengthen the capacity of residents in facing the challenges of cross-interest communication and collaboration, especially in terms of policy advocacy and local resource management. The service subjects consisted of local community groups who had been less involved in the decision-making process at the village level. The service process is carried out through several stages, starting from joint problem mapping, training in negotiation and lobbying techniques, to the preparation of collaborative action plans that involve active participation of residents. The findings from this activity show that interest-based negotiation and ethical lobbying can strengthen the community's bargaining position towards external actors such as the government and local stakeholders. The dynamics of the activity also resulted in initial social changes, such as the formation of an internal advocacy group, increased participation in public forums, and the emergence of collective awareness of the importance of strategic communication.